Co-ensiling garlic stalk with citrus pulp improves the fermentation quality and feed-nutritional value - Lee, Youn Hee (Asian-Australasian journal of animal sciences, 2020)
OBJECTIVE: Ensiling is a simple and effective method for long-term preservation; however, less information exists about the ensilability characteristics of garlic stalk (GS). Therefore, the objectives were to examine the ensiling feasibility of GS